High-reliability hash-chain based broadcast method in wireless network for factory automation. (2017) - Luo, Xinqiang; Qi, Yue; Wan, Yadong; Wang, Qin
Authentication is important to broadcast, which is a widely-used communication method in wireless network for factory automation. Traditional hash-chain based methods maintain long key chains for authentication. However, these methods face the trade-off between the broadcast amount supported and huge storage of the key chain. This paper presents a high-reliability secure broadcast method TuTESLA based on multiple hash chains. First, multiple-transmission is applied to improve the reliability of broadcast; second, multiple hash chains are introduced and the structure of them are optimised to eliminate the dependence between the length of chains and the amount of the broadcasts supported. Compared with the traditional methods based on hash chain, in the security aspect, TuTESLA has comparable message security and key security, and higher replay-attack protection, but weaker resistance to denial of service attacks; in the overhead aspect, TuTESLA has much lower storage overhead, but slightly higher computing and communication overhead.